2014
DOI: 10.4103/0975-7406.137256
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoids - Clinical effects and applications in dentistry: A review

Abstract: Flavonoids include a huge group of naturally occurring organic compounds. It is found in a large variety of plants including fruits, seeds, grains, tea vegetables, nuts, and wine. Many studies have shown that there is a strong association between flavonoid intake and the long-term effects on mortality. It is widely used in dentistry and it has many clinical effects. This article summarizes the effects of flavonoids to humankind and its clinical applications in dentistry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 16 publications
0
22
0
2
Order By: Relevance
“…Flavonoids are a group of natural polyphenols with the structure of diphenylpropane (C6C3C6) skeleton that are widely distributed in many plant foods, such as fruits, vegetables, nuts, seeds, grains and tea (Kandaswami et al, 2005;Sankari et al, 2014). According to the structural difference, flavonoids can be classified as flavones, flavonols, flavanones, isoflavones, catechins or flavanols, anthocyanidins, and so on (Ross and Kasum, 2002).…”
Section: Introductionmentioning
confidence: 98%
“…Flavonoids are a group of natural polyphenols with the structure of diphenylpropane (C6C3C6) skeleton that are widely distributed in many plant foods, such as fruits, vegetables, nuts, seeds, grains and tea (Kandaswami et al, 2005;Sankari et al, 2014). According to the structural difference, flavonoids can be classified as flavones, flavonols, flavanones, isoflavones, catechins or flavanols, anthocyanidins, and so on (Ross and Kasum, 2002).…”
Section: Introductionmentioning
confidence: 98%
“…The pharmacological functions of flavonoid compounds include multiple-treatment effects against various systematic diseases, including cardiovascular, neurological, immunological, endocrinology, and respiratory symptoms (Chavez-Santoscoy et al, 2014;Daddam et al, 2014;Sankari et al, 2014). These studies also revealed promising treatment effects of flavonoid compounds against liver damage.…”
Section: Discussionmentioning
confidence: 94%
“…Recently, promising results in the treatment of liver fibrosis have been reported using Chinese medicine (Li et al, 2014b;Zhang et al, 2014a), which often contain flavonoid compounds (Fu et al, 2014). Current studies have revealed multiple pharmacological roles of flavonoid compounds, including the treatment of tumors, cardiovascular disease, and diabetes (Chavez-Santoscoy et al, 2014;Daddam et al, 2014;Sankari et al, 2014). To further study the effect of flavonoid compounds extracted from Iris plants on liver fibrosis, we developed liver fibrosis model rats using carbon tetrachloride (CCl 4 ) and measured indices of liver function, liver fibrosis, and tissue pathological changes to evaluate their effects on CCl 4 -induced rat liver fibrosis.…”
Section: Introductionmentioning
confidence: 99%
“…Usually, flavonoids in plants are combined with one or more sugar molecules and known as flavonoid glycosides [24]. Accumulating evidence suggests that flavonoids exhibit extensive pharmacological effects and biological effects in vitro and in vivo including antioxidant, 5 anti-inflammation, anti-microbial, anti-tumor, anti-asthma, anti-adipogenesis and anti-diarrhea [19,20,[23][24][25][26]. Because of the potential beneficial effects of flavonoids on human health, foods rich in flavonoids have attracted great interest recently [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…They are widely distributed in human diets such as fruits, vegetables, wine, seeds or roots of plants [19,20]. Up to now, more than 7000 varieties of flavonoids have been identified and can be classified as flavones, flavonols, flavanones, isoflavones, flavan-3-ols and anthocyanidins according to their structural difference [21,22].…”
Section: Introductionmentioning
confidence: 99%